Mitigation of the Stranded Asset Risk Due to the Implementation of Coal Plants Early Retirement in Indonesia Using Analytical Hierarchy Process - Bagus Nugroho; Dony Abdul Chalid (Quantitative Economics and Management Studies, 2024)
Based on Presidential Regulation Number 112 of 2022 concerning the Acceleration of Renewable Energy Development for the Supply of Electric Power, Indonesia has a road map in which there is a strategy program for accelerating the end of the operational period of PLTUs. In implementing early retirement, there is a risk of stranded assets that needs to be mitigated. Appropriate decision-making strategies and effective mitigation are needed to reduce the impact of stranded asset risk. Using the Anaytical Hierarchy Process (AHP), this study tries to analyze the implementation of the PLTU early retirement strategy by taking into account the risk of stranded assets and finding appropriate mitigation in reducing the level of impact of the risk of stranded assets that needs to be implemented by stakeholders. The results show that effective mitigation requires comprehensive planning and stakeholder involvement, which can substantially ease the financial transitions from coal to renewable energy sources. The findings suggest that integrating economic and policy considerations into the early retirement planning of coal-fired power plants is crucial for managing the transition effectively and minimizing potential financial losses. This approach ensures a smoother transition to sustainable energy sources, contributing significantly to both national and global decarbonization goals.